Tumor infiltrating CD8(+) T lymphocyte count is independent of tumor TLR9 status in treatment naïve triple negative breast cancer and renal cell carcinoma - Mella, Mikko (Oncoimmunology, 2015)
Toll-like receptor 9 (TLR9) is a cellular DNA-receptor of the innate immune system that is widely expressed in cancers. We demonstrated that low tumor TLR9 expression predicts poor disease-specific survival in triple negative breast cancer (TNBC) and renal cell carcinoma (RCC). We hypothesized that this is because TLR9 expression affects tumor immunophenotype. To begin to test this, we compared the number of tumor infiltrating CD8(+) T lymphocytes with TLR9 expression in treatment naïve breast cancer (n = 197) and RCC (n = 94) cohorts with known TLR9 expression status. CD8(+) T lymphocyte counts were assayed with image analysis after immunohistochemistry (IHC). Tumor TLR9 expression was not correlated with CD8(+) T cell counts in breast cancer or RCC. CD8(+) T cell counts were significantly associated with tumor proliferation index in TNBC, but not in non-TNBC. CD8(+) T cell counts were also significantly associated with tumor grade in non-TNBC, but not in TNBC. In RCC, CD8(+) T cell counts were significantly associated with tumor stage. CD8(+) T cell counts were significantly associated with prognosis in TNBC and RCC, but the presence of CD8(+) T cells in these tumors had opposite effects on disease-specific survival: High CD8(+) counts were associated with better prognosis in TNBC and worse prognosis in RCC. Among TNBC patients, those with low tumor TLR9 and low CD8(+) T cell counts had the poorest prognosis (log-rank p = 0.0002 vs. high tumor TLR9 and high CD8(+) T cell count). In conclusion, pre-treatment tumor TLR9 status is not associated with tumor infiltrating CD8(+) T lymphocytes in TNBC or RCC. The combination of TLR9 and CD8(+) TIL count might be a novel composite prognostic marker in TNBC.